Soybean hulls in roughage-free diets for limit-fed growing cattle - C.A. Löest; D.J. Bindel; Evan C. Titgemeyer; James S. Drouillard; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred heifers (573 lb initial body weight) were used in a growing study to compare growth performance of cattle fed roughage-free diets comprised mainly of soybean hulls with that of cattle receiving roughage- and corn-based diets and to determine if cattle fed soybean hull-based diets would respond to supplemental methionine hydroxy analogue (MHA; a source of methionine), ruminally protected betaine, or concentrated separator by-product (CSB; a source of betaine). Treatments included 1) a roughage-based diet fed at 2.75% of body weight (ROUGH), 2) a corn-based diet fed at 1.5% of body weight (CORN1.5), 3) a corn- based diet fed at 2.25% of body weight (CORN2.25), 4) a soybean hull-based diet fed at 1.5% of body weight (SH1.5), 5) a soybean hull-based diet fed at 2.25% of body weight (SH2.25), 6) SH1.5 top-dressed with 11.4 g/head daily MHA, 7) SH2.25 top-dressed with 11.4 g/head daily MHA, 8) SH2.25 top-dressed with 7 g/head daily rumenprotected betaine, and 9) SH2.25 top- dressed with 250 g/head daily CSB. Supplemental MHA, betaine, and CSB did not change feed intakes, gains, or feed efficiencies for cattle fed soybean hulls. Heifers fed soyhulls at 2.25% of body weight gained 27% slower (P<.01) than heifers fed the corn-based diet at similar intakes and were 25% less efficient (P<.01). Similar results were observed for cattle fed soybean hulls and corn at 1.5% of body weight. Cattle fed soybean hulls at 2.25% of body weight had gains similar to those of cattle receiving the roughage-based diet at 2.75% of body weight, but feed efficiencies tended to be better (P=0.11) for the cattle receiving soybean hulls because less feed was consumed. The roughage-fed cattle gained 23% less (P<.01) than cattle fed corn at 2.25% of body weight and were 34% less efficient.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Soybean hulls; Heifers; Performance; Feedlot